Prevalence, correlates, and prospective predictors of non-suicidal self-injury among New Zealand adolescents: cross-sectional and longitudinal survey data. Issue 1 (December 2015) - Garisch, Jessica; Wilson, Marc
Abstract Non-suicidal self-injury (NSSI) is common among adolescents and linked to many maladaptive outcomes. This study aimed to assess the prevalence and correlates of NSSI among a community sample of New Zealand adolescents. A self-report questionnaire was administered to adolescents at time 1 (N = 1162, mean age = 16.35), and approximately five months later (time 2, N = 830, mean age = 16.49). Prevalence and bivariate correlations were assessed at both time points, and cross-lag correlations using matched data (N = 495, mean age = 16.23). Lifetime history of NSSI was 48.7 % (females 49.4 %, males 48 %). Consistent with previous international research, NSSI was associated with higher Alexithymia, depression, anxiety, bullying, impulsivity, substance abuse, abuse history and sexuality concerns and lower mindfulness, resilience and self-esteem. Cross-lag correlations suggested NSSI is directly (perhaps causally) related to psychological vulnerability in various domains (e.g., increased depression and lower self-esteem), while bullying may be more distal to NSSI, rather than a proximal predictor.